Non-destructive assessment of leaf composition as related to growth of the grapevine (Vitis vinifera L. cv. Shiraz) - Strever, Albert (Albert Erasmus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD(Agric))--Stellenbosch University, 2012